Language Planning Activities and Policy – the Case of Poland - Kuźniak, Marek; Mańczak-Wohlfeld, Elżbieta (Glottodidactica, 2016)
The paper examines the way and the extent to which language policies have affected the development of the Polish language especially in recent times, since the so-called end of the communist era. The discussion revolves round the Polish Language Act of 1999 which set the rules appropriate to ‘protecting’ Polish from ‘foreign influences’ (English in particular). Subject to examination is the Act’s origins, the government’s motives for it, as well as amendments the Act has undergone since it was first promulgated in 1999 and the justifications for them. Finally, the paper addresses various practical implications stemming from the Act and manifested in a number of more or less spectacular actions taken by the competent bodies and authorities in order to protect the Polish language.